Annual Plan 1969-70 Government of India Planning Commission - Planning Commission (Planning Commission, 1969)
The Annual Plan for 1969-70 marks the resumption of phased development of the economy through Five Year Plans. The Fourth Five Year Plan (1969-74) came in effect on April 1, 1969. The Annual Plan for 1969-70 is for the initial year of that Plan. This document sets out in some detail the programmes and schemes to be implemented during 1969-70 by the various State Governments, Administrations of Union Territories and the Central Government in the context of the overall tasks outlined in the Fourth Five Year Plan (Draft). Developmental activities in the private sector are also broadly covered.
Government of India, Planning Commission